Abdulrahman Al-Youbi, Adnan H.M. Zahed, William G. Tierney (Eds), Successful Global Collaborations in Higher Education Institutions, Springer, Cham 2020, pp. 101 - Adamczewski, Jakub (Studia Edukacyjne, 2021)
Recenzja